Aspergillus niger-mediated release of phosphates from fish bone char reduces Pb phytoavailability in Pb-acid batteries polluted soil, and accumulation in fenugreek. (15th November 2022) - Tauqeer, Hafiz Muhammad; Basharat, Zeeshan; Adnan Ramzani, Pia Muhammad; Farhad, Muniba; Lewińska, Karolina; Turan, Veysel; Karczewska, Anna; Khan, Shahbaz Ali; Faran, Gull-e; Iqbal, Muhammad
Abstract: Soil receiving discharges from Pb-acid batteries dismantling and restoring units (PBS) can have a high concentration of phytoavailable Pb. Reducing Pb phytoavailability in PBS can decline Pb uptake in food crops and minimize the risks to humans and the environment. This pot study aimed to reduce the concentration of phytoavailable Pb in PBS through Aspergillus niger ( A. niger )−mediated release of PO4 3− from fish bone [Apatite II (APII)] products. The PBS (Pb = 639 mg kg −1 soil) was amended with APII powder (APII−P), APII char (APII−C), and A. niger inoculum as separate doses, and combining A. niger with APII−P (APII−P +  A. niger ) and APII−C (APII−C +  A. niger ). The effects of these treatments on reducing the phytoavailability of Pb in PBS and its uptake in fenugreek were examined. Additionally, enzymatic activities and microbial biomass carbon (MBC) in the PBS and the indices of plant physiology, nutrition, and antioxidant defense machinery were scoped. Results revealed that the APII−C +  A. niger treatment was the most efficient one. Compared to the control, it significantly reduced the Pb phytoavailability (DTPA-extractable Pb fraction) in soil and its uptake in plant shoots, roots, and grain, up to 61%, 83%, 74%, and 92%. The grain produced under APII−C +  A. niger were safe for human consumption as Pb concentration in grain was 4.01 mg kg −1 DW, remaining within the permissible limit set by WHO/FAO (2007). The APII−C +  A. niger treatment also improved soil pH, EC, CEC, MBC, available P content and enzymatic activities, and the fenugreek quality parameters. A. niger played a significant role in solubilizing PO4 3− from APII−C, which reacted with Pb and formed insoluble Pb-phosphates, thereby reducing Pb phytoavailability in PBS and its uptake in plants. This study suggests APII−C +  A. niger can remediate Pb-polluted soils via reducing Pb phytoavailability in them. Graphical abstract: Image 1 Highlights: Pb immobilization was tested in soil polluted by effluents from Pb-acid batteries. Soil treatments were APII−P, APII−C, A. niger, APII−P +  A. niger and APII−C +  A. niger. APII−C +  A. niger treatment was leading to reducing Pb phytoavailability in soil. Fenugreek quality and soil enzymatic activities were enhanced in this treatment. Pb content in fenugreek grain with APII−C +  A. niger met the WHO/FAO standards.